Comparison of cutting tool insert's made of oxide cutting ceramic machining of grey cast iron - Kovalcik, Jaroslav (Manufacturing Technology Journal, 2009)
In this article there you can find comparisons of several types of cutting tool insert's of oxide cutting ceramics machining of grey cast iron. Experiments had to serve the realization of long-term durability tests. Very important angle for balance was the index of Taylor's equation that represents the influence of cutting speed on the durability and power optimization. By experimenting, there were discovered precious features of some kinds of compared cutting tool insert's and their references to the power optimization for machining grey cast iron.
Keywords: machining of metal; cutting ceramics; durability; tool wear